"...OUR STRUGGLE FOR FREEDOM IS SO DIFFICULT AND BLOODY": PROSE ABOUT THE FIRST WORLD WAR IN ANTHOLOGY ATTEMPT - Mocherniuk, N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The Russian-Ukrainian war, the disaster of which our nation is currently experiencing, sharpened interest in the relevant literature. "War" has become the key word by which the readership orients itself in the whirlwind of writing - both non-fiction and fiction. And indeed, there is no shortage of "war" books: in the first month of aggression, the creative forces of Ukrainians seemed to freeze, writers held their breath from the audacity and meanness of the enemy, words froze, and later survived, were reborn to convey the fragility of the historical moment, everything suffered and experienced . Poetry collections "Poetry without shelter" have already been published, a kind of "anthology of national resistance", as stated in the abstract, which collects the impressions of the first month of a full-scale war. Other collections are also being prepared. Oksana Pukhonska’s literary work "Beyond the Battle. Discourse of war in modern literature". Events such as the scientific and artistic form "Muses are not silent", organized by the Institute of Literature, signaled the activation of the creative forces of Ukrainians.